Reliability Evaluation of Behavioral Representations from Multimedia Applications - An Experimental Approach - Prota, Thiago Monteiro; Silva, Douglas Veras da; Ferraz, Carlos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
There are several efforts that seek to provide abstractions to represent the behavior of multimedia applications, each with its limitations and complexity. In this scenario, it is common to provide abstractions based on state machines, because they adequately define the behavioral transitions of these applications. However, it is not trivial to identify the real state machine from application. In this context, reliability is quite critical, given the applicability of these abstractions in many activities. In this work, we present a controlled experiment to evaluate the reliability of the state-based representation of multimedia applications, applying an approach in evaluating a real solution that extracts the behavioral model from the source code of NCL applications. Our approach uses a finite representative set of sequences defined by a test-cases generation technique in the evaluation process.